IMMU-01. TEM-GBM: AN OPEN-LABEL, PHASE I/IIA DOSE-ESCALATION STUDY EVALUATING THE SAFETY AND EFFICACY OF GENETICALLY MODIFIED TIE-2 EXPRESSING MONOCYTES TO DELIVER IFN-A WITHIN GLIOBLASTOMA TUMOR MICROENVIRONMENT. (21st September 2021) - Finocchiaro, Gaetano; Eoli, Marica; Gentner, Bernhard; Capotondo, Alessia; Anghileri, Elena; Antonarelli, Gabriele; Barcella, Matteo; Bruzzone, Maria Grazia; Carrabba, Matteo; Cuccarini, Valeria; D'Alessandris, Quintino G; DiMeco, Francesco; et al.
Abstract: Temferon is a macrophage-based treatment relying on ex-vivo transduction of autologous HSPCs to express immune-payloads within the TME. Temferon targets the immune-modulatory molecule IFN-a, to a subset of tumor infiltrating macrophages known as Tie-2 expressing macrophages (TEMs) due to the Tie2 promoter and a post-transcriptional regulation layer represented by miRNA-126 target sequences. As of 31 st May 2021, 15-patients received Temferon (D+0) with follow-up of 3 – 693 days. After conditioning neutrophil and platelet engraftment occurred at D+13 and D+13.5, respectively. Temferon-derived differentiated cells, as determined be the number of vector copy per genome, were found within 14 days post treatment and persisted albeit at lower levels up to 18-months. Very low concentrations of IFN-a in the plasma (8.7 pg/ml-D+30) and in the CSF (1.6 pg/ml-D+30) were detected, suggesting tight regulation of transgene expression. Five-deaths occurred at D+322, +340, +402, +478 and +646 due to PD, and one at D+60 due to complications following the conditioning regimen. Eight-patients had progressive disease (range: D-11 to +239) as expected for this tumor type. SAEs include GGT elevation (possibly related to Temferon) and infections, venous thromboembolism, brain abscess, hemiparesis, seizures, anemia and general physical condition deterioration, compatible with ASCT, concomitant medications and PD. Four-patients underwent 2 nd surgery. Recurrent tumors had gene-marked cells and increased expression of ISGs compared to first surgery, indicative of local IFNa release by TEMs. In one patient, a stable lesion had a higher proportion of T cells and TEMs within the myeloid infiltrate and an increased ISGs than in the progressing lesion, detected in the same patient. Tumor-associated clones expanded in the periphery. TME characterization by scRNA and TCR-sequencing is ongoing. To date, Temferon is well tolerated, with no DLTs identified. The results provide initial evidence of Temferon potential to activate the immune system of GBM patients, as predicted by preclinical studies.